ANALISIS YURIDIS PROSES PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) BERDASARKAN SURAT KEPUTUSAN BERSAMA 3 MENTERI TENTANG PTSL PADA BADAN PERTANAHAN NASIONAL KABUPATEN LABUHANBATU - Bernat Panjaitan; Risdalina Siregar; Maya Jannah; Ahmad Badawi harahap; Santi Rambe (Universitas Labuhanbatu, 2022)
Complete Systematic Land Registration is the legalization of assets in the form of land leveling activities for the first time in the context of issuing land rights certificates for all community groups, especially middle and low economic groups. This study aims to determine whether land leveling through the PTSL Program carried out in Labuhanbatu Regency can run smoothly and is in accordance with applicable regulations. This research includes empirical legal research, where data is collected by means of literature studies and research to the location of the object of research and conducting interviews with relevant sources. The results of this study are the importance of the local government making a legal umbrella in the form of a regent regulation that discusses in detail the PTSL process in villages so that there is no extortion by village officials, especially for the poor, it can be expected to be free from the cost of issuing certificates of property rights through the PTSL program funded by the local government, but in its implementation of course there are obstacles, both technical and juridical, such as regional conditions, community aspects and others. The suggestion given by the author is that there should be more active socialization of intentions to the public, both through print and electronic media about the importance of registering land rights to obtain proof of ownership rights in the form of certificates. Likewise, the village government must carry out its duties so that the people in the area live in prosperity and can succeed in carrying out and completing the Systematic Complete Land Registration (PTSL) so that the land owned by the community is clearly guaranteed legal certainty, orderly administration and avoids disputes.Keywords: Juridical Analysis; Registration; Land.